A REVIEW ON OPTIONS OF REDUCING GREENHOUSE GASES EMISSION FROM ENERGY SECTOR - Utami Irawati (Program Studi Kimia, Universitas Lambung Mangkurat, 2010)
Climate change has influenced many sectors whereas energy sector is a crucial aspect uniquely interrelated with it. Recently, the rising global awareness about climate change and how it can affect the world has influenced the way people use and produce energy. Nevertheless, reducing the use of energy as a practical way of reducing green house gases (GHG) is not as simple as one might expect. Energy might be the main source of GHG emission. But on the other hand, as illustrated by UNEP in Global Outlook Report 2006, energy is also the main fuel of world development. This article aims to review attempts to search best ways of reducing GHG emission to mitigate the effect of climate change from energy sector. Increasing energy efficiency and using technology to provide “clean” energy are two among those attempts. Despite the good intention of those attempts, their applications have not yet showed the expected result of a significant reduction in GHG emission. These efforts are often restrained in their implementation by a number of factors, where economic considerations come as the most dominant factors.A continuous effort of developing technologies that support energy efficiency and clean energy provision is a crucial need. Along with it, there should also be a major reform in changing the way people behave toward energy itself.Keywords: GHG emission, energy efficiency, alternative sources of energy